Comparison study of existing bowl piston and modified bowl piston diesel engine performance emission and combustion characteristics by using diesel - Manikalithas, P.; Venkatachalam, R.; KalilRahiman, M.; Bharathiraja, M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this investigation, the Modified bowl piston (MBP)diesel engine performanceemission and combustion characteristics have been studied by using diesel (100%D)and compared with theExisting bowl piston (EBP). From the results, it is evident that the MBP has given higher brake thermal efficiency (BTE) at an engine load 80%, 100% and higher exhaust gas temperature (EGT) has been given in engine all loads, when compared with EBP. In emission point of view,the MBP has given lower hydrocarbon (HC),carbon monoxide (CO), smoke at all loads when compared with EBP, However nitrogen oxide (NOX), carbon dioxide (CO2)have increased for MBP. In the combustion point of view MBP has given higher cylinder pressure (CP) and higher cumulative heat release rate (CHRR) at full load condition when compared with EBP. Â From the experimental results, it has been concluded that the MBP is anapt one in performance, emission and combustion perspective when compared with EBP by using 100%D.